Multidomain Cognitive Training Transfers to Attentional and Executive Functions in Healthy Older Adults - Gajewski, Patrick D.; Thönes, Sven; Falkenstein, Michael; Wascher, Edmund; Getzmann, Stephan (Frontiers in Human Neuroscience, 2020)
Healthy aging is associated with deficits in focused and sustained attention and executive functions. However, cognitive training provides a promising method to counteract these deficits. In the present randomized controlled study, we examined to what extent cognitive training regimes can improve attention, verbal skills and inhibition capacities. Over a period of 16 weeks, healthy older adults (65 years and older, mean: 70 years) received a trainer-guided multidomain paper & pencil and computerized cognitive training. Pre- and post-training, a battery of psychometric tests was applied that measured the critical functions. This study used two control groups: a passive control and an active control group performing a relaxation training. Compared to a passive control group, the cognitive training led to enhanced performance in the attentional endurance test and the interference list of the Stroop test whereas no benefits in verbal and crystalized tests were found. Similar effects were found on the attentional endurance compared to the active control group. Additionally, word fluency was enhanced after CT but the improvement in Stroop test did not reach significance compared to the active control. The contents of cognitive training were dissimilar to the psychometric tests showing far transfer, whereas no transfer to attentional or memory functions in the daily life assessed by the Cognitive Failures Questionnaire was found. This demonstrates specific gains of multidomain cognitive training on cognitive functions not explicitly trained and lack of transfer to daily activities.